EVALUASI KELAYAKAN DAN KESIAPAN HUNIAN PADA RUMAH SUSUN KEJAKSAAN TINGGI PROVINSI SUMATERA SELATAN - Dian Sefriansyah; Kiagus Muhammad Aminuddin; Arie Putra Usman (LATERAL: Jurnal Teknik Sipil, 2026)
The government has an obligation to provide apartment housing for the public, particularly for low-income communities (MBR), civil servants (ASN), and other vulnerable groups. Coordination challenges among stakeholders have become a key focus in realizing livable, efficient, and sustainable vertical housing. This study aims to ensure that the apartment building constructed at the High Prosecutor’s Office is deemed habitable and can be occupied immediately. The research was conducted at the High Prosecutor’s Office of South Sumatra Province. The objective is to assess the feasibility and readiness of the apartment housing at the South Sumatra High Prosecutor’s Office, in accordance with the Regulation of the Minister of Public Works and Housing (PUPR) Number 07 of 2022 concerning the implementation of Housing Development Assistance and special housing provided by the government.The evaluation results of the housing feasibility assessment at the South Sumatra High Prosecutor’s Office produced a score of 78.50 (Good). Based on this evaluation, improvements are necessary to meet housing feasibility standards, particularly in the areas of window and door frames, doors, windows, walls, ceilings, access roads, water systems, and waste disposal systems.